Efektivitas Penggunaan Ice Breaking dalam Pembelajaran Daring pada Mata Kuliah Ilmu Tauhid - Oktio Frenki Biantoro; Ruwandi Ruwandi; Muhammad Munif (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
Online learning impacts students' lack of motivation to learn as daily learning is spent in front of the gadget. That causes student saturation, so a way is needed to have a strong motivation in learning. The study aims to determine the use, effectiveness, and impact of ice breaking in online learning of Tauhid courses. Data collection techniques used were in-depth interviews, observations, and documentation. At the same time, the interactive data analysis model technique popularized by Miles and Huberman was used. This research found that the ice breakings used in online learning of Tauhid courses were: ice breaking based on clapping the limbs, ice breaking based on exercise, and ice breaking based on humour. In addition, the use of ice breaking in online learning of Tauhid courses was considered adequate. It also positively impacted more fluid online learning, increased student interest in learning, and pushed student activity.